Pruebas regionales - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
The seventh testing cycle for promising CIAT selections under improved, low-input technology was completed in 1981 at 9 locations in Colombia. The overall av. yield of the trials was 8.5 t/ha/yr, which is nearly 3 times the national av. yield of 3-3.5 t/ha. Av. yield of local cv. was about twice this national av. with 6.5 t/ha. The av. yield of best performing CIAT selections in each location was 12.9 t/ha. Cv. CM 507-37 outyielded the best local cv. by nearly 100 percent in all 9 locations. Best local var. were: in Media Luna, cv. Secundina (5.6 t/ha); in Chigorodo, Patepaba (6.0 t/ha); in Carimagua, Llanera (2.1 t/ha); in Rionegro and Nataima, Venezolana (6.3 and 9.9 t/ha, resp.); in San Martin, Tempranera (4.6 t/ha); in Florencia, Caquetena (6.4 t/ha); in CIAT-Palmira, M Col 113 (5.2 t/ha); and in Caicedonia, Chiroza Gallinaza (13.4 t/ha). Cassava yields can be raised up to 400 percent with improved cultural practices and on-site selection of the best CIAT genotype. Results obtained during 7 yr of regional trials show that CIAT genotypes have yielded consistently higher than local var. In regional trials 1980/81 in Cuba, Haiti, Dominican Republic, Mexico,Honduras, Costa Rica, Venezuela, Ecuador, Bolivia, the Philippines, and USA (Florida), cv. M Col 1468 (CMC 40) and M Col 1684 were outstanding for their high fresh root yields (av. of 24.2 and 22.4 t/ha, resp.). The effect of planting date (May vs. Sept.) on root yield was compared at Media Luna. The Sept. planting produced 2.4 t more DM/ha than the May planting. This difference could be attributed to the heavier infestation of diseases and pests in the May planting. Planting material produced at Media Luna, Carimagua, and Rio Negro yielded higher than stakes produced at CIAT. Leaf-bud propagation and the transferability of technology to farmers were also studied. (CIAT)